The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

The effect of rhizosphere pH on removal of naphthenic acid fraction compounds from oil sands process-affected water in a willow hydroponic system - Mitchell E. Alberts; Ralph Hindle; Camryn Charriere; Amanda L. Schoonmaker; Heather Kaminsky; Douglas G. Muench (Science of The Total Environment, 2024)

Research on biodeteriotration of plastics - Ji-Dong Gu; Tim Ford; Bryce Mitton; Ralph Mitchell (International Biodeterioration & Biodegradation, 2024)

Machine learning-based estimation of cognitive performance using regional brain MRI markers: the Northern Manhattan Study - Michelle R. Caunca; Lily Wang; Ying Kuen Cheung; Noam Alperin; Sang H. Lee; Mitchell S. V. Elkind; Ralph L. Sacco; Clinton B. Wright; Tatjana Rundek (Brain Imaging and Behavior, 2021)

Correction to: Bilingualism Is Associated with a Delayed Onset of Dementia but Not with a Lower Risk of Developing it: a Systematic Review with Meta-Analyses - Stefano Brini; Hamid R. Sohrabi; Jeffrey J. Hebert; Mitchell R. L. Forrest; Matti Laine; Heikki Hämäläinen; Mira Karrasch; Jeremiah J. Peiffer; Ralph N. Martins; Timothy J. Fairchild (Neuropsychology Review, 2020)
The original version of this article unfortunately contained the following mistakes.

Bilingualism Is Associated with a Delayed Onset of Dementia but Not with a Lower Risk of Developing it: a Systematic Review with Meta-Analyses - Stefano Brini; Hamid R. Sohrabi; Jeffrey J. Hebert; Mitchell R. L. Forrest; Matti Laine; Heikki Hämäläinen; Mira Karrasch; Jeremiah J. Peiffer; Ralph N. Martins; Timothy J. Fairchild (Neuropsychology Review, 2020)
Some studies have linked bilingualism with a later onset of dementia, Alzheimer’s disease (AD), and mild cognitive impairment (MCI). Not all studies have observed such relationships, however. Differences in study outcomes may be due to methodological limitations and the presence of confounding factors within studies such as immigration status and level of education. We conducted the first systematic review with meta-analysis combining cross-sectional studies to explore if bilingualism might delay symptom onset and diagnosis of dementia, AD, and MCI. Primary outcomes included the age of symptom onset, the age at diagnosis of MCI or dementia, and the risk of developing MCI or dementia. A secondary outcome included the degree of disease severity at dementia diagnosis. There was no difference in the age of MCI diagnosis between monolinguals and bilinguals [mean difference: 3.2; 95% confidence intervals (CI): −3.4, 9.7]. Bilinguals vs. monolinguals reported experiencing AD symptoms 4.7 years (95% CI: 3.3, 6.1) later. Bilinguals vs. monolinguals were diagnosed with dementia 3.3 years (95% CI: 1.7, 4.9) later. Here, 95% prediction intervals showed a large dispersion of effect sizes (−1.9 to 8.5). We investigated this dispersion with a subgroup meta-analysis comparing studies that had recruited participants with dementia to studies that had recruited participants with AD on the age of dementia and AD diagnosis between mono- and bilinguals. Results showed that bilinguals vs. monolinguals were 1.9 years (95% CI: −0.9, 4.7) and 4.2 (95% CI: 2.0, 6.4) older than monolinguals at the time of dementia and AD diagnosis, respectively. The mean difference between the two subgroups was not significant. There was no significant risk reduction (odds ratio: 0.89; 95% CI: 0.68–1.16) in developing dementia among bilinguals vs. monolinguals. Also, there was no significant difference (Hedges’ g = 0.05; 95% CI: −0.13, 0.24) in disease severity at dementia diagnosis between bilinguals and monolinguals, despite bilinguals being significantly older. The majority of studies had adjusted for level of education suggesting that education might not have played a role in the observed delay in dementia among bilinguals vs. monolinguals. Although findings indicated that bilingualism was on average related to a delayed onset of dementia, the magnitude of this relationship varied across different settings. This variation may be due to unexplained heterogeneity and different sources of bias in the included studies. Registration: PROSPERO CRD42015019100.

Towards a molecular basis of oligometastatic disease: potential role of micro-RNAs - Abhineet Uppal; Mark K. Ferguson; Mitchell C. Posner; Samuel Hellman; Nikolai N. Khodarev; Ralph R. Weichselbaum (Clinical & Experimental Metastasis, 2014)

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

Oligogenic combinations associated with breast cancer risk in women under 53years of age - Christopher E. Aston; David A. Ralph; Dominique P. Lalo; Sharmila Manjeshwar; Bobby A. Gramling; Daniele C. DeFreese; Amy D. West; Dannielle E. Branam; Linda F. Thompson; Melissa A. Craft; Debra S. Mitchell; Craig D. Shimasaki; et al. (Human Genetics, 2005)

Indigenous microflora and opportunistic pathogens of the freshwater zebra mussel, Dreissena polymorpha - Ji-Dong Gu; Ralph Mitchell (Hydrobiologia, 2002)

Experimental Pathogenicity of Aeromonas spp. for the Zebra Mussel, Dreissena polymorpha - James S. Maki; Gayatri Patel; Ralph Mitchell (Current Microbiology, 1998)

Differentiation between Gallionella and Metallogenium - Fraser Walsh; Ralph Mitchell (Archives of Microbiology, 1973)